2018
DOI: 10.1159/000492354
|View full text |Cite
|
Sign up to set email alerts
|

miR-27b Suppresses Endothelial Cell Proliferation and Migration by Targeting Smad7 in Kawasaki Disease

Abstract: Background/Aims: Increasing evidence indicates that microRNAs (miRNAs) play important roles in Kawasaki disease (KD). Our previous study demonstrated that hsa-miR-27b-3p (miR-27b) was up-regulated in KD serum. However, the specific role of miR-27b in KD remains unclear. We aimed to investigate that miR-27b could be a biomarker and therapeutic target for KD treatment. As well, the specific mechanism of miR-27b effecting endothelial cell functions was studied. Methods: The expression of miR-27b and Smad7 was mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
29
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(30 citation statements)
references
References 31 publications
0
29
1
Order By: Relevance
“…mir-27b could modulate the expression of target genes at the posttranscriptional level (25,28,29). in the present study, we hypothesized whether mir-27b regulated the progression of ali through specific target genes.…”
Section: Discussionmentioning
confidence: 80%
“…mir-27b could modulate the expression of target genes at the posttranscriptional level (25,28,29). in the present study, we hypothesized whether mir-27b regulated the progression of ali through specific target genes.…”
Section: Discussionmentioning
confidence: 80%
“…Previous studies have established that morpholino‐based knockdown of gpr126 expression in zebrafish results in hypotrabeculation at 80 h postfertilization (hpf) . Because of its previously reported regulation of genes involved in heart development, miR‐27b was chosen as a candidate for performing in vivo experiments . Therefore, we injected zebrafish miR‐27b in single cell–stage Tg(myl7:EGFP‐Hsa.HRAS) embryos and analyzed their hearts at 80 hpf (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…A detailed literature analysis further supports that miR‐27b regulates Gpr126 expression. miR‐27b and Gpr126 are both expressed during heart development and in endothelial cells, are both shear stress–regulated, and associated with cognitive impairment or intellectual disability, as well as bladder cancer . In addition, it is known that Gpr126 is expressed in the salivary gland, lung, and kidney, while miR‐27b is associated with non‐small cell lung cancer, clear cell renal cell cancer, and adenoid cystic carcinoma of the salivary glands .…”
Section: Discussionmentioning
confidence: 99%
“…ese results therefore plainly indicate that the miR-27b-ACOT2 axis promotes lipid accumulation and adipocyte di erentiation, process which result in NAFLD pathogenesis. Several studies have shown that miR-27b regulates not only adipogenesis, but also cell proliferation, angiogenesis, and tumor development [14,15,40,41]. Nonetheless, the role of miR-27b has not been fully elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, the role of miR-27b has not been fully elucidated. For example, upregulated miR-27b in the serum of Kawasaki disease patients enhanced endothelial cell proliferation and migration by targeting Smad7 [40]. In contrast, down-regulated miR-27b promoted the activation of adenosine monophosphate-activated role in cancer metastasis [37].…”
Section: Discussionmentioning
confidence: 99%